The Clinical and Genetic Features of Co-occurring Epilepsy and Autism Spectrum Disorder in Chinese Children - Long, Shasha; Zhou, Hao; Li, Shuang; Wang, Tianqi; Ma, Yu; Li, Chunpei; Zhou, Yuanfeng; Zhou, Shuizhen; Wu, Bingbing; Wang, Yi (Frontiers in Neurology, 2019)
There is still a lack of a comprehensive description of the general population regarding clinical features and genetic etiology for co-occurred epilepsy and autism spectrum disorder in Chinese children. This was a retrospective study of children diagnosed with epilepsy and ASD from January 1st, 2015 to May 1st, 2018 in the Children’s Hospital of Fudan University. A total of 117 patients met inclusion criteria; 103 subjects were eligible. Among them, 88 underwent genetic testing and 47 children (53.4%) were identified as having pathogenic or likely pathogenic variants: 39 had single gene mutations (83.0%, 39/47) and eight had copy number variants (17.0%, 8/47), with SCN1A (14.9%, 7/47) and MECP2 (10.6%, 5/47) gene mutations being the most common. Mutations in other genes encoding voltage-gated ion channels including SCN2A, CACNA1A, CACNA1H, CACNA1D, and KCNQ2 were also common but the number of individual cases for each gene was small. Epilepsy syndrome and epilepsy-associated syndrome were more common (P = 0.012) and higher rates of poly-therapy (P = 0.002) were used in the positive genetic test group than in the negative group. There were no differences in intractable seizure, ASD severity, and intellectual disability degree between the positive genetic test group and the negative genetic group. These data strongly indicate the need for ASD screening in voltage-gated ion channel gene mutation epilepsy patients for better diagnosis and early intervention.